Evaluation Of Halal Certification Implementation In Improving Product Quality At CV. Werry Group Gunungsitoli - Ndruru, Fihabudi; Zai, Kurniawan Sarototonafo; Mendrofa, Martha Surya Dinata; Duha, Tiarni (Journal of Management, Economic, and Accounting, 2025)
In this study, researchers found that consumer confidence in products is still not optimal, especially among people who pay close attention to halal aspects when choosing products. The research was conducted using observations at CV. Werry Group Gunungsitoli. This study employed a qualitative method through interviews with informants. The objectives of this research were to evaluate the implementation of halal certification, identify the challenges in implementing halal certification, and propose strategies that CV. Werry Group Gunungsitoli could adopt to optimise the benefits of halal certification in enhancing product quality. The research findings revealed compliance with the requirements for halal certification. The challenges in the implementation process include the lengthy processing time, which can take up to 3 to 6 years. The strategies implemented include displaying the halal logo on packaging, developing new halal products, and positioning halal certification as the primary selling point in promotions.